2016
DOI: 10.1007/s11136-016-1344-0
|View full text |Cite
|
Sign up to set email alerts
|

Applying generalizability theory methods to assess continuity and change on the Adolescent Quality of Life-Mental Health Scale (AQOL-MHS)

Abstract: Purpose The Adolescent Quality of Life Mental Health Scale (AQOL-MHS) is designed to measure quality of life in clinical samples of Latino adolescents aged 12–18 years. Initial findings support its reliability, validity and conceptual model for use of its three domains (Emotional Regulation, Self-Concept, and Social Context). Our current study tests the usefulness of the AQOL-MHS for tracking changes in HRQOL during the course of service use. Methods Three waves of data were collected from 59 participants wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Lakes and Hoyt (2009) have argued that G Theory is a particularly useful conceptual framework for measuring the stable and transient components of a latent construct among adolescents where development is paramount. A recent paper by Chavez et al, (2016) demonstrated this approach with the Adolescent Quality of Life-Mental Health Scale (AQOL-MHS) in adolescents attending mental health clinics assessed on three occasions over eight months. The focus of that study was on the reliability of change scores and the authors used a method developed by Cranford et al (2006) based on G Theory to compare conventional estimates of reliability (Cronbach's alpha, test-retest) with GT estimates.…”
Section: Stable Versus Transient Features Of Depressionmentioning
confidence: 99%
“…Lakes and Hoyt (2009) have argued that G Theory is a particularly useful conceptual framework for measuring the stable and transient components of a latent construct among adolescents where development is paramount. A recent paper by Chavez et al, (2016) demonstrated this approach with the Adolescent Quality of Life-Mental Health Scale (AQOL-MHS) in adolescents attending mental health clinics assessed on three occasions over eight months. The focus of that study was on the reliability of change scores and the authors used a method developed by Cranford et al (2006) based on G Theory to compare conventional estimates of reliability (Cronbach's alpha, test-retest) with GT estimates.…”
Section: Stable Versus Transient Features Of Depressionmentioning
confidence: 99%
“…While all measures identified in this systematic review were constructed using classical test theory, there are other measurement models that might be more suitable to measuring compulsive exercise such as item response theory and generalizability theory, which would allow for separation of systematic from unsystematic errors, and for both norm-referenced and criterion-referenced outcomes [ 61 , 62 ]. Future instruments may benefit from a different theoretical underpinning to explore alternative measurement models.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we also applied Generalizability Theory (G theory) to investigate the score dependability of the FACT-Hep, which addresses the dependability of measurements and the simultaneous estimation of multiple sources of variance including interactions [28][29][30]. We employed a random effects design for both the G-study and D-study in measurement mode to estimate the variance components and dependability coe cients using a one-facet crossed design: persons (p) by items (i), represented as p x i, where the patients as the object of measurement and not a source of error and not considered a facet, but the items as one facet of measurement error.…”
Section: Discussionmentioning
confidence: 99%